The Effect of Project-Based Learning on 21st Century Skills in Middle School Students in Indonesia - Rahman, Rashid; Zaki, Amin; Pratama, Yoga Anjas (Yayasan Pedidikan Islam Daarut Thufulah, 2025)
In the context of global educational transformation, the integration of 21st-century skills into learning practices has become imperative, particularly for preparing students to face complex challenges in the modern era. This study investigates the effect of Project-Based Learning (PjBL) on the development of 21st-century skills—critical thinking, collaboration, creativity, and communication—among middle school students in Indonesia. The objective of the research is to determine whether PjBL significantly enhances these competencies compared to conventional instructional methods. A quantitative approach with a quasi-experimental design was employed, involving two groups of Grade 8 students from a public middle school in West Java. The experimental group received instruction through PjBL, while the control group experienced traditional teaching. Data were collected using a 21st-century skills rubric and analyzed using independent sample t-tests. The findings revealed that students exposed to PjBL demonstrated significantly higher performance in all four skill domains. These results underscore the effectiveness of PjBL as a student-centered approach that fosters meaningful learning experiences aligned with real-world contexts. In conclusion, Project-Based Learning has a positive and significant impact on the enhancement of 21st-century skills in middle school students and is recommended for broader implementation in Indonesian education.